العجائبية بين الواقع والخيال (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
لعلّ اختراق قوانين الواقع , والولوج إلى عوالم خفية, سيفضي بالضرورة إلى دلالات جديدة, ومن شأن ذلك أن يصرف الذهن إلى الفصل بين الواقع والخيال كحدين متناقضين ضمن إطار العجائبية. وجل ما أتوخاه , في هذا البحث , أن يستطيع القارئ إدراك طبيعة العلاقة بين الواقع والخيال, وأن تتكون لديه صورة لأهمية الخيال , ودوره الفاعل في التعبير عما يمور في المجتمع من متغيرات , وما يعانيه الإنسان بسببها من مشكلات نفسية , تجعل حياته – في أغلب الأحيان – غير مفهومة ولا معقولة . To penetrate the laws of reality and access the hidden factors will necessarily lead to new meanings, and that would make the mind separate between reality and fiction as two contradictory poles within the framework of the miraculous. What I intend in the research is to make the reader be able to understand the nature of the relationship between reality and fiction, and to realize the importance of imagination and its active role in expressing the changes in society, and the psychological problems that the human being suffers, which make their life, in most cases, not understandable nor reasonable.